(untitled) (Beacon: International Journal of Education and Social Studies, 2026)
This study investigates the relationship between institutional inclusion strategies, public policy implementation, and the mental well-being of university students with disabilities in higher education. Using a quantitative, descriptive-correlational design, data were collected from 350 students with disabilities enrolled in public and private universities. The instruments included a structured questionnaire measuring institutional inclusion strategies and psychological well-being based on Ryff’s model. Data were analyzed using descriptive statistics, Pearson correlation, and independent-samples t-tests. The results reveal a significant positive correlation between institutional inclusion strategies and mental well-being (r = 0.68, p < 0.001). Curricular adaptations and technological accessibility showed the strongest associations with psychological well-being. Students in private universities reported higher levels of inclusion and well-being compared to those in public institutions. Furthermore, students with psychosocial disabilities exhibited lower levels of mental well-being than other disability groups. The findings highlight the importance of effective institutional strategies and robust public policies in promoting inclusive higher education environments that support both academic participation and psychological well-being. The study contributes to understanding how inclusive practices influence student well-being and provides implications for policy development and institutional improvement.